Pelatihan Guru Dalam Penggunaan Internet di Sekolah Dasar Tahfidz Qur'an Adz-Zikra - Rizalina Rizalina; Elvira Sawitri; Afni Nia Sari (LPPM Universitas Dharma Andalas, 2023)
Abstract In today's era, namely the era of globalization, technology is developing rapidly. Along with the development of information and communication technology, especially the internet with all its functions including surfing, browsing, e-mail, cloud storage has become a necessity for many people. One of the effects of globalization in the field of information technology is to facilitate a job, including in the world of education. The internet assists teachers in finding information, making interesting teaching materials and being able to convey them to students as attractively as possible and being able to store these teaching materials and share them with fellow teachers and students. Utilization of IT can make it easier for teachers to be more creative and innovative in developing subject matter in class. With the use of the Internet the need for information can be carried out more quickly, easily and efficiently so that understanding and mastery in its use are needed. Implementation of this Community Service in the form of counseling and training for Tahfidz Qur'an Adz-Zikra Elementary School teachers is useful for increasing the ability to operate the Internet so that teachers can obtain teaching materials that are up to date and interesting which makes the learning process expected to be more effective and efficient as well as creating space for teachers and students to engage in a more enjoyable teaching and learning system. Keywords: Training, Internet, Google Drive, Teachers, Teaching Materials.